Effects of the economic reactivation in Colombia - Vallejo Zamudio, Luis E. (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The economic crisis that faces Colombia on behalf of the Coronavirus pandemic is huge. Expectations of reactivation of different economic sectors are growing. Although it is true that a rebound in May compared to April was observed, statistics released by the Colombian bureau of statistics (DANE, by its acronym in Spanish) for the first half of this year are dramatic. DANE predicts that production at the end of 2020 will fall 10% and employment 20%.